EFEKTIVITAS METODE OUTDOOR STUDY (KELAS EDUKASI SORE) DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS SISWA KELAS 1 SDN 04 NAGARI TALANG TANGAH - Leni Zahara , Darmila , Nida Khoeru Ummah , Dini Amelia; Widya Rahma Suci , Hasnul Zafra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning motivation of first-grade elementary students in English subjects is still relatively low, as seen from their lack of active participation and enthusiasm in class. This study aims to determine the effect of the Outdoor Study method in the afternoon education class program on students’ learning motivation in English. The research used a quantitative approach with a One Group Pretest-Posttest Design. The sample consisted of 20 first-grade students from SDN 04 Nagari Talang Tangah. The instrument used was a learning motivation questionnaire administered before and after the intervention. The treatment involved teaching English using the Outdoor Study method over three weeks, covering topics such as alphabet recognition, basic emotions, and body parts through fun and interactive outdoor activities. The results showed a noticeable increase in students’ learning motivation after the implementation of the Outdoor Study method, as evidenced by a significant difference between pretest and posttest results. Normality and homogeneity tests confirmed that the data met the requirements for parametric analysis, and the paired samples t-test showed a statistically significant difference in learning motivation. These findings align with the theory of experiential learning, which emphasizes that meaningful learning occurs when students actively experience the learning process. Thus, the Outdoor Study method proves to be effective in enhancing elementary students’ motivation, especially in learning English. This study recommends the Outdoor Study as a contextual and suitable learning method for young learners.